2019
DOI: 10.1093/jcr/ucz036
|View full text |Cite
|
Sign up to set email alerts
|

Contraction with Unpacking: When Unpacking Leads to Lower Calorie Budgets

Abstract: Consumers set a lower consumption budget when they set individual calorie budgets for constituent categories (e.g., breakfast, lunch, dinner, and snacks; categorical approach) versus when they set a total budget (overall approach). This contraction effect of unpacking a judgment is driven by motivated reasoning. Consumers are motivated to reduce calorie consumption, and this motive directs their cognitive elaboration for the budget decision to be on what to cut and how much to cut. Furthermore, the categorical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Previous studies have confirmed Amazon Mechanical Turk as a source of acceptable and generalizable data (Cheung et al , 2017; Paolacci et al , 2010; Paolacci and Chandler, 2014). Consequently, many high-quality research outlets have relied on the results of studies drawing their data solely from Amazon Mechanical Turk (Beck et al , 2020; Jia et al , 2020; Stuppy et al , 2020). Therefore, although online studies present more limitations compared to real field experiments, randomly choosing our sample from Amazon Mechanical Turkers did not undermine the quality of our results.…”
Section: General Discussion and Implicationsmentioning
confidence: 99%
“…Previous studies have confirmed Amazon Mechanical Turk as a source of acceptable and generalizable data (Cheung et al , 2017; Paolacci et al , 2010; Paolacci and Chandler, 2014). Consequently, many high-quality research outlets have relied on the results of studies drawing their data solely from Amazon Mechanical Turk (Beck et al , 2020; Jia et al , 2020; Stuppy et al , 2020). Therefore, although online studies present more limitations compared to real field experiments, randomly choosing our sample from Amazon Mechanical Turkers did not undermine the quality of our results.…”
Section: General Discussion and Implicationsmentioning
confidence: 99%
“…Jia et al. (2020) look at how individual calorie budgets can be function of the budgeting approach—whether the calorie budget is set for the day or per meal. They find that the budget is lower if set by meal.…”
Section: Discussionmentioning
confidence: 99%
“…By drawing on a motivated cognition perspective, this research provides fresh insights into the reasons for consumer misbehaviour. Second, previous research has applied motivated recognition theory to study issues related to consumer behaviour and business ethics (Lin et al, 2020;Jia et al, 2020;Rees et al, 2022). However, its application is still insufficient in these research fields.…”
Section: Imds 1232 596mentioning
confidence: 99%
“…Given the importance of motivated cognition for individuals' decision-making, motivated cognition theory has been applied to consumer behaviour (Lin et al. , 2020; Jia et al. , 2020; Rees et al.…”
Section: Theoretical Backgroundmentioning
confidence: 99%